Poland and the Treaty of Trianon – an Outline of the Issue - Lubocki, Adam; Fodor, Áron Szabolcs (Vade Nobiscum, tom XXIII/2021: Studia nad XIX i XX wiekiem, 2021)
The authors of this article have tried to present some issues concerning the Treaty of Trianon (1920). The first one is made up by the resolutions of the document which is called the ‘peace dictate of Trianon’ by Hungarians, and their reception in Hungary in the interwar period has also been analysed. This issue is still not well-known enough in the collective consciousness of Poles. The second significant issue is related to a problem which is controversial in Polish historiography: this is the question whether Poland ratified the Treaty of Trianon since she was obliged to do it. The opinions concerning this topic are ambiguous. Therefore, the presentation of the opinions of each of the historians provides the opportunity to give an idea of this issue. The authors conclude their article by presenting some information on the act of signing the treaty on 4th June, 1920 from the perspective of Polish newspapers, with a special regard to newspapers in Galicia being geographically the closest ones, and the most detailed ones which described the events in Hungary.